Konsep Ummatan Wasatan dan Muqtasid Menurut Wahbah Az-Zuhaili (Studi Kitab Tafsir Al-Munir) - Juwita, Putri; Mustafa, Ilham (Lembaga Yasin AlSys, 2023)
The author's background in conducting this research is that there are several problems that befell the Indonesian people in the name of religion, especially Islam. Such as cases of violence, extremism in religious radicalism, terrorism which are getting more complicated day by day. Even though the Qur'an explains how to act in the middle and not be too excessive in various aspects of life. A middle or moderate attitude in religion is described in the Qur'an either with the term ummatan wasatan (wasathiyyah) or with the term ummatan muqtasid. These two terms are not only intended for Muslims but also for people of the book, namely Jews and Christians. These two terms are analyzed based on the interpretation of Wahbah az-Zuhaili in the book of tafsir al-Munir. The type of research that the author uses is the library research method, while the method used is the maudhu'i (limited thematic) research method, namely a research method based on certain themes in the Koran. The results of this research are according to Wahbah Zuhaili in the book of tafsir al-Munir what is meant by ummatan wasatan in the QS. al Baqarah verse 143 is a fundamental point in Islam which contains the meaning of middle class, justice, balance, praiseworthy character, not being excessive in religion and not being negligent in fulfilling one's obligations as well as combining knowledge and charity, the spirit of fighting for justice, teaching balance in various aspects of life and upholding human dignity and dignity. Meanwhile, the term ummatan muqtasid in QS. al-Maidah: 66 according to Wahbah az-Zuhaili is moderate in actions, namely being on the straight path and not exceeding limits. Therefore, from what Wahbah az-Zuhaili explains in his interpretation, it indicates that the concept of ummatan wasathan and muqtasid refers to people who have a middle or balanced attitude in all things, which is in line with human nature, namely being able to combine the physical and spiritual, knowledge and charity and not exceeding limits or hurting other people in the life of religion, nation or state.